COMPARATIVE LEGAL REPRESENTATION OF COSTS OF CIVIL PROCEEDINGS, AS THE SUBJECT OF PROVIDING REDRESS IN GERMAN AND CROATIAN LAW - Nakić, Jakob (Glasnik Advokatske komore Vojvodine, 2021)
Costs of civil proceedings may constitute a significant financial burden for the parties in exercising their rights. Ensuring redress enables transferring this burden “to the back” of the insurer and thus facilitating the parties' conduct of civil proceedings in financial terms, which is also of influence on the possibility of exercising their rights. Providing redress covers only those legal costs that are necessary (necessary) to achieve protection of the legal interests of the insured. At the same time, the insurer reimburses legal expenses in accordance with the provisions of the procedural laws on the duty to compensate the costs of proceedings and regulations determining the amount and content of individual legal costs. The paper deals with the presentation and analysis of the coverage of legal sums in German law. Then, along with the model of the analysed coverage under German law, the coverage of the costs of redress in Croatian law is presented, while processing elements of legal costs (certain legal acts prescribed to pay appropriate fees, as well as the amount of such fees) which the legal protection insurers should take into account when forming the cover of the OP. Finally, the case law of the Court of Justice of the European Union relating to ensuring redress is presented.
Keywords: provision of redress, conditions of insurance, civil costs, legal costs, court costs